Non-invasive prediction of tissue Doppler-derived E/e′ ratio using lung Doppler signals. (12th June 2020) - Benjamin, Mina M; Bianco, Christopher; Caccamo, Marco; Sokos, George; Kagiyama, Nobuyuki; Shrestha, Sirish; Verzosa, Grace; Sengupta, Partho P
Abstract: Aims: Lung Doppler signals (LDS) represent the radial movement of small pulmonary blood vessel walls, caused by pulse waves of cardiac origin. We sought to investigate the accuracy and prognostic value of LDS as a predictor of mitral valve early diastolic flow to annular velocity ratio ( E / e ′), in patients with acute decompensated heart failure (ADHF). Methods and results: We prospectively enrolled patients with ADHF ( n  = 99, mean age 65 ± 15 years, 61% males) who underwent echocardiographic and simultaneous LDS evaluation at hospital admission. Patients with hospital stay over 72 h underwent a repeat echocardiogram and LDS assessment before discharge. Patients were followed for the occurrence of short-term all-cause mortality and heart failure (HF) hospitalization. Predicted E / e ′ from LDS correlated with echocardiographic E / e ′ at admission and discharge ( r  = 0.67 and 0.83; P  < 0.001 for both), respectively. Patients were dichotomized into two groups by the median predicted- E / e ′. A high predicted- E / e ′ was associated with age, hypertension, anaemia, history of HF with preserved ejection fraction (EF), and chronic kidney disease. Over a median follow-up period of 7 months, 22 (22.2%) patients died and 23 (23.2%) patients were rehospitalized for HF. Kaplan–Meier analysis revealed a significantly lower event-free survival in high predicted- E / e ′ group HF patients with reduced EF ( P  = 0.0247). No significant differences were observed in HF rehospitalization rates between the two groups. Conclusion: In this single-centre prospective study of patients with ADHF, LDS predicted echocardiographic E / e ′ measurements and showed prognostic value in predicting all-cause mortality in HF patients with a reduced EF.